Electrodeposition and corrosion behavior of nanocrystalline aluminum from a chloroaluminate ionic liquid. Issue 11 (14th April 2015) - Sheng, P.‐F.; Chen, B.; Shao, H.‐B.; Wang, J.‐M.; Zhang, J.‐Q.; Cao, C.‐N.
<x xml:space="preserve">Abstract</x> The effect of 2‐chloronicotinyl chloride on the electrodeposition of Al in the ionic liquid [Emim]Cl/AlCl3 was first investigated. The results of cyclic voltammograms indicated that 2‐chloronicotinyl chloride produced the inhibiting effect on the Al deposition, which could be ascribed to its adsorption on the electrode surface. The nanocrystalline and microcrystalline Al films on low carbon steel substrate were prepared by square‐pulse current electrodeposition in the ionic liquid [Emim]Cl/AlCl3 with and without 2‐chloronicotinyl chloride, respectively. A highly uniform and smooth Al film with average crystalline size of 15 nm and a goldish shining surface was obtained in the ionic liquid with 0.5 g L−1 2‐chloronicotinyl chloride. The electrodeposited Al films in 3.5 wt.% NaCl solution presented much more negative corrosion potentials (Ecorr) than the bare carbon steel, indicating the cathodic protective action of the Al films with respect to the carbon steel substrate. The corrosion density of the nanocrystalline Al film was much lower than that of the microcrystalline Al film, suggesting the superior corrosion resistance of the nanocrystalline Al film. The excellent anticorrosion performance of the nanocrystalline Al film could be attributed to its unique nanocrystalline structure and highly smooth surface characteristics.